2014
DOI: 10.1179/1743132814y.0000000453
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple coaxial catheter system on transvenous embolization for dural arteriovenous fistula

Abstract: 1 2Background: Although transvenous embolization (TVE) is an effective method for 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Triple and quadruple coaxial systems have been described to overcome the long and tortuous route. 11,12 However, in previous reports, an unusual access route from the external jugular vein via anastomosis with the STV and FV to the SOV has not been described. Hayashi et al 12 reported the usefulness of the quadruple coaxial system for transvenous embolization of CSdAVF, but they did not describe the details of the venous access route in four recruited cases of CSdAVF.…”
Section: Discussionmentioning
confidence: 99%
“…Triple and quadruple coaxial systems have been described to overcome the long and tortuous route. 11,12 However, in previous reports, an unusual access route from the external jugular vein via anastomosis with the STV and FV to the SOV has not been described. Hayashi et al 12 reported the usefulness of the quadruple coaxial system for transvenous embolization of CSdAVF, but they did not describe the details of the venous access route in four recruited cases of CSdAVF.…”
Section: Discussionmentioning
confidence: 99%